Gain equalization of EDFA using a loop filter with a single polarization controller - Zhou, Kejiang (2013)
A Sagnac loop filter with two pieces of high birefringence fiber having equal lengths, and spliced together at a fixed angle of 30o displacement between the two principle axes, is proposed in this letter. Gain equalization of erbium-doped fiber amplifiers (EDFAs) is implemented by tuning only the polarization controller in the loop filter. Experimental result shows that there remains a deviation of ± 1 dB in the region of the flattened profile with the useful bandwidth of about 23 nm, thereby demonstrating the effectiveness of the method. An effective mathematical model and mechanism is also given for further explanation.